In vitro seed germination of paphiopedilum lowii, an endangered slipper orchid in North Borneo - Vinishaa S. Ragu; Roslin Ombokou; Rimi Repin; Duni Molidin; Ramlan Miadin; Zaleha Abdul Aziz (Society for Indonesian Biodiversity, 2022)
Paphiopedilum lowii (Lindl.) Stein is alarmingly decreasing in numbers due to habitat destruction and over-collection. Propagation through seed is one effort to conserve the species. In vitro method offers better results for seed germination in orchids, but the success of germination is species-specific. Hence, this research aimed to evaluate different types of media [(½ strength Murashige & Skoog and Orchimax Medium (Duchefa Biochemie)], and to determine the effects of sucrose [0% 1%, 2% and 3% (w/v)], peptone [0%, 0.1% and 0.2% (w/v)], coconut water [0%, 10%, 20% and 30% (v/v)] and fertilizer [Orchid Focus-0%, 0.1% and 0.2% (v/v)] on seed germination. The protocorm size was also determined after 12 weeks of observation. Half-strength MS media consistently gave higher seed germination, ½ MS supplemented with 1% (w/v) sucrose, 0.1% (w/v) peptone, 0% (v/v) coconut water and 0.1 % (v/v) fertilizer resulted in the highest seed germination at 5.32% ± 5.9, 19.27% ± 9.34, 11.33% ± 3.80 and 19.31% ± 9.03 respectively. Despite being 12 weeks in culture, the sizes of the protocorms are small (0.222±0.089 mm diameter, 0.703±0.280 mm circumference, and 0.045±0.043 mm2 area); this requires future investigation. These findings can serve as base information for further enhancement of seed germination and development of propagation methods of P. lowii for use in a conservation program. © 2022, Society for Indonesian Biodiversity. All rights reserved.